2007
DOI: 10.1039/b711990a
|View full text |Cite
|
Sign up to set email alerts
|

Water uptake of hydrophilic polymers determined by a thermal gravimetric analyzer with a controlled humidity chamber

Abstract: The moisture uptake of several water-soluble polymers at different humidities was investigated with a thermal gravimetric analyzer equipped with a controlled humidity chamber. The water sorption of poly(acrylic acid) sodium salt, poly(ethylene glycol) and silica, which are known as super absorbers, were examined. In addition, various hydrophilic polymeric materials were selected according to their structural features. These included hydroxyl functions on the side chains (e.g. poly(2-hydroxyethyl methacrylate))… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
103
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(111 citation statements)
references
References 45 publications
8
103
0
Order By: Relevance
“…The amount of adsorbed water is potentially considerable, since at 90% RH and at a temperature of 20 ºC, bulk pNIPAM is capable of adsorbing a maximum of ~8% of its own weight in water. 55 Now for all of the probes, we see dramatic changes in the log(I N* /I T* ) ratio (Figure 5a), greater red shift of the N* band (Figure 4), decreases in fluorescence intensity (Figure 2), but no significant change in local heterogeneity experienced by the excited states (Figure 3c) ([fwhm, decreases for N* state, indicating a reduction in heterogeneity of the emitting states]. So this second phase hydration produces spectral effects similar to those produced by the common solvent polarity effect with increasing dielectric stabilization of the N* state causing a greater red shift of the N* band, and a large relative increase in the log(I N* /I T* ) ratio.…”
Section: Bandmentioning
confidence: 99%
“…The amount of adsorbed water is potentially considerable, since at 90% RH and at a temperature of 20 ºC, bulk pNIPAM is capable of adsorbing a maximum of ~8% of its own weight in water. 55 Now for all of the probes, we see dramatic changes in the log(I N* /I T* ) ratio (Figure 5a), greater red shift of the N* band (Figure 4), decreases in fluorescence intensity (Figure 2), but no significant change in local heterogeneity experienced by the excited states (Figure 3c) ([fwhm, decreases for N* state, indicating a reduction in heterogeneity of the emitting states]. So this second phase hydration produces spectral effects similar to those produced by the common solvent polarity effect with increasing dielectric stabilization of the N* state causing a greater red shift of the N* band, and a large relative increase in the log(I N* /I T* ) ratio.…”
Section: Bandmentioning
confidence: 99%
“…This delayed moisture absorption of PET RCM 1 compared with PET R 1 can be attributed to a similar suggestion made previously about an "incubation" period needed until CM complexes start to absorb water. A similar concept was reported in Thijs et al 2007; there, the formation of a "first hydration shell" on dried hydrophilic polymers, conditioned under various RH values, was conjured to explain sharp increases in the moisture uptakes of these polymers. In the same study it was concluded that there was a certain difficulty in the formation of a first hydration shell, after which additional hydration shells could form more easily.…”
Section: Moisture Sorption/desorptionsupporting
confidence: 71%
“…Therefore, they could retain moisture for longer periods of time, and could possibly be used in slow release systems. On the other hand, the limited hysteresis of PET RM 1 is not surprising; isothermic curves of similar shape have been reported for pure PNIPAAm (Thijs et al 2007). The lower moisture uptake values of PET RM 1, compared with PET RCM 1, can be attributed to the almost continuous layer that microgel M forms on polyester.…”
Section: Moisture Sorption/desorptionsupporting
confidence: 61%
See 1 more Smart Citation
“…Note that poly(acrylic acid) sodium salt and poly(ethylene oxide) were reported to absorb a little moisture under relatively dry conditions (30°C, 40% RH; water uptake <5 wt %); in contrast, poly(ECH-MeIm + Cl ¹ ) is deliquescent at similar conditions (vide supra). 27 With regards to the contribution of the counter anion, poly(N-glycidyl-N¤-methylimidazolium bis(trifluoromethanesulfonyl)imide) (M n(calc) = 11300; DP = 27) (poly(ECH-MeIm + TFSI ¹ )) was hydrophobic (23°C, 40% RH; water uptake <0.2 wt %). To summarize, the deliquescent character of the present cationic polyethers is supposed to be derived from the combination of both the imidazolium halide group and polyether chain.…”
mentioning
confidence: 99%